Two serious ladies - Bowles, Jane, 1917-1973 (HarperCollins, 2014)
"Christina Goering, eccentric and adventurous, and Frieda Copperfield, anxious but enterprising, are two serious ladies who want to live outside of themselves. Old friends, each will take a surprising path in search of salvation: during a visit to Panama, Mrs. Copperfield abandons her husband, finding solace in a relationship with a teenage prostitute; while Miss Goering, a wealthy spinster, pursues sainthood via sordid encounters with the basest of men. At the end the two women meet again, each radically altered by her experience"--Provided by publisher.